Technology of cultivation and care of strawberries - Anvarbekova Charos Anvarbek qizi; Rahimova Mo‘tabar Rustamjon qizi; Esonova Surayyo Ilyos qizi (Zien Journals, 2022)
The importance of strawberries. Recommended varieties of strawberries. Planting scheme and timing, preparation and transplanting of land for strawberry planting. Pests and their control. Harvest.
Keywords: strawberries; vitamins; cultivation; planting